Cullin-5 deficiency promotes chimeric antigen receptor T cell effector functions potentially via the modulation of JAK/STAT signaling pathway - Yoshitaka Adachi; Seitaro Terakura; Masahide Osaki; Yusuke Okuno; Yoshitaka Sato; Ken Sagou; Yuki Takeuchi; Hirofumi Yokota; Kanae Imai; Peter Steinberger; Judith Leitner; Ryo Hanajiri; et al. (Nature Communications)
Abstract Chimeric antigen receptor (CAR) T cell is a promising therapy for cancer, but factors that enhance the efficacy of CAR T cell remain elusive. Here we perform a genome-wide CRISPR screening to probe genes that regulate the proliferation and survival of CAR T cells following repetitive antigen stimulations. We find that genetic ablation of CUL5, encoding a core element of the multi-protein E3 ubiquitin-protein ligase complex, cullin-RING ligase 5, enhances human CD19 CAR T cell expansion potential and effector functions, potentially via the Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway. In this regard, CUL5 knockout CD19 CAR T cells show sustained STAT3 and STAT5 phosphorylation, as well as delayed phosphorylation and degradation of JAK1 and JAK3. In vivo, shRNA-mediated knockdown of CUL5 enhances CD19 CAR T treatment outcomes in tumor-bearing mice. Our findings thus imply that targeting CUL5 in the ubiquitin system may enhance CAR T cell effector functions to enhance immunotherapy efficacy.